Afghanistan halfway through the transition phase: Shortcomings of the security transition and remaining options for NATO - Nils Wörmer (Stiftung Wissenschaft und Politik (SWP), 2013)
Progress with regard to building up Afghanistan's National Security Forces, improving the governance performance of the incumbent regime, pursuing a domestic peace process, cooperating with Afghanistan's neighbors (particularly Pakistan and Iran), and creating prospects for economic development have been defined as preconditions for the successful transition of security responsibilities in Afghanistan. However, one and a half years after the security transition phase was officially launched by the Afghan government, NATO has been experiencing severe difficulties in the outlined fields of activity. US policy and NATO's strategy toward Afghanistan seem at least partly deadlocked. Western policymakers have few remaining options for the second half of the security transition in Afghanistan. These include focusing on the two key players in the Afghan conflict, namely strengthening the government of the Islamic Republic of Afghanistan and weakening the senior leadership of the Afghan Taleban
Keywords: 320